Distribuição e orientação dos quimiorreceptores de O2 branquiais em tilápia-do-Nilo (Oreochromis niloticus): controle das respostas cardiorrespiratórias à hipóxia - Zeraik, Vivian Maria (2012)
In fish the O2 chemoreceptors are mainly found in the gill arches and monitor the O2 tensions (PO2) of the inspired water (externally oriented) and/or the arterial blood (internally oriented). During hypoxia these receptors trigger cardiorespiratory adjustments in order to maintain an adequate O2 transfer to the tissues. The aim of the present study was to determine the O2 chemoreceptors distribution through the gill arches of Nile tilapia and the role of these receptors on the cardiorespiratory responses to hypoxia in this species. One buccal and two opercular canullae, and a pair of ECG electrodes were implanted in a group of intact fish (control group, n = 10; Wt = 258.4 ± 7.4 g). This procedure served to measure the following cardiorespiratory variables: respiratory frequency - fR, ventilatory tidal volume - VT, gill ventilation - VG , O2 extraction from the ventilatory current EO2, oxygen uptake - VO2 , and heart rate fH. After an overnight recovery period from surgery fish were subjected to the following O2 tensions during 40 min each: 140 (normoxia), 100, 70, 50, 30 e 20 mmHg. To verify the O2 receptors distribution in the gills, the first pair of gill arches was surgically extirpated (operated group, n = 10; Wt = 232.5 ± 8.8 g). After a recovery period of 4 days, operated fish were subjected to the same procedures described above for the intact ones. To examine the orientation of these receptors, other intact (n = 10; Wt = 259.6 ± 6.2 g) and operated (n = 10; Wt = 248.7 ± 6.5 g) groups had a PE catheter implanted into the buccal cavity, another catheter implanted inside the caudal vein and fitted with ECG electrodes to measure the following variables: ventilatory amplitude (Vamp), fR, and fH. Two internal injections (administered through the cannula into the caudal vein): a) 0.5 mL intravenous saline (0.9%), b) 0.5 mL intravenous NaCN (750 μg.mL-1 of NaCN in saline) and two external injections (injected by oral cannula): c) 1 mL H2O, d) 1 mL NaCN (750 μg.mL-1 of NaCN in water) were administered in both groups. The VO2 of operated fish was significantly lower only in severe hypoxia. Both bradycardia, and respiratory parameters were not abolished by ablation of the first pair of gill arches. EO2 of operated group remained about 18% lower than that of control group. The responses to internal and external NaCN included decreases in fH and increases in fR and Vamp. The cardiorespiratory parameters were attenuated in the operated group, indicating the presence of chemoreceptors, but not limited to the first gill arch. In Nile tilapia the O2 chemoreceptors are distributed beyond the first gill arch, probably through the four gill arches. Furthermore, these receptors are internally and externally oriented, possibly along all gill arches, triggering the cardiorespiratory adjustments necessary to face the hypoxic conditions at which the species is frequently subjected in its natural environmental conditions.